Observed changes in heavy daily precipitation over the Nordic-Baltic region - Anita Verpe Dyrrdal (Elsevier, 2021)
Study region: The Nordic-Baltic region has experienced numerous flooding episodes resulting from heavy rainfall. Such events are costly and may potentially threaten the safety of the population. In this paper we present a temporally long and spatially dense dataset of annual maximum daily precipitation and their date of occurrence measured in a large region covering Fennoscandia and the Baltics (Dyrrdal et al., 2021, doi:10.11582/2021.00015). Study focus: We analyse the long-term (1901–2020) changes at 138 stations and short-term (1969–2020) changes at 724 stations for both annual maxima and their date of occurrence. Further, we assess the climatology of heavy precipitation including record evens, as well as changes in design values. New hydrological insight for the region: Results show a majority of positive trends in daily annual maxima and the 5-year return level, with hotspots in southeast of Norway, southern Sweden and southwest of Finland. Generally, annual maximum precipitation events occur somewhat later in the year now compared to the beginning of the last century. The 5-year return level is relatively homogeneous across the Nordic-Baltic region, with values between 30 and 50 mm, except for a few lower values in Finland and high values mainly exceeding 70 mm at the west coast of Norway.